Implementasi Jaringan Wireless Mesh Berbasis Protokol Babel Untuk Video Streaming Menggunakan Codec H.264 - Hilkya Dwima Palembangan; Widhi Yahya; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wireless mesh network is a network consisting of several devices that are connected to each other to send and receive data, and act as a relay for sending data on a small network scope. Because video streaming process in a network requires connection between the server and the client that runs continuously and real time, so the codec used, the size of the video, and the location of the server and client affect the quality of video streaming results. Recommended standards for video streaming to run smoothly is that the jitter value is no more or equal to 10 ms to 50 ms, and packet loss is not more than 0.5%. In this study, testing of video streaming is carried out on a wireless mesh network based on Babel routing protocol with a limited number of devices using H.264 and MJPEG codecs. The quality of network service in each test scenario is determined in the form of delay, throughput, jitter, and packet loss, then the test results between H.264 and MJPEG codecs are compared. After testing, H.264 codec has packet loss value of 2.14% while the MJPEG codec has packet loss value of 5.03%. H.264 codec has a jitter value of 164154.38 ms while the MJPEG codec has a jitter value of 305.67 ms. H.264 codec has a throughput value of 0.016 MB/s while MJPEG codec has a throughput value of 0.047 MB/s. H.264 codec has a delay value of 0.036 ms while the MJPEG codec has a delay value of 0.0306 ms. Jitter and packet loss value from testing using the H.264 codec do not meet the recommended standard values for video streaming.